Empathy and Other Ways of Not Understanding: In Search of a Socially Transformative Relationality. - Guy Smith (Think Pieces, 2014)
To download this article, please click here. This article considers the need for ‘new relational modes’ as means to produce a durably less destructive global society. Three unorthodox ‘listening practices’ (all from the field of psychotherapy) are selected for consideration: two from (different versions of) psychoanalysis, and a verbal method called ‘rooted talking’ from Biodynamic Body Psychotherapy. The practices are compared and contrasted, their conflict on the topic of ‘empathy’ identified, and a strategic truce proposed. The article establishes that the three practices are allied in their eschewal of ‘meaning’ and ‘understanding’ and in their critiques of meaning-centred communication. These critiques are then linked to Leo Bersani’s critique of identity (personal, national, gendered etc.) as intrinsically destructive. The author argues that a culture of communication practices centred exclusively on meaning is dangerous, since our inherited field of meaning defines us in hierarchical binaries (e.g. white/black, man/woman) that divide, oppose and so embattle us. The author proposes that frequent practice of speaking and listening modes not centred on meaning would keep us mindful of the arbitrariness of all categories, while providing us with pleasures beyond the identitarian. Propagation of such practices beyond the institution of psychotherapy, therefore – as modes of everyday intercourse – may be of significant social value.